Edukasi Tehnik Stretching Exercise Terhadap Peningkatan Fleksibilitas pada Tungkai Bawah: The Education of Stretching Exercise Techniques for Increasing the Flexibility on Lower Limbs - Yudiansyah Yudiansyah (IKesT Muhammadiyah Palembang, 2022)
Stretching is placing certain parts of the body so that it can increase the length of certain muscles and soft tissues or is usually referred to as stretching muscles. One of the stretching exercises that can be used before activities to increase flexibility and prevent injury is static stretching exercises. Static stretching exercises are stretching one or more muscle groups by moving the body position and then maintaining that position for some time that has been set. The purpose of this program is to provide health education as an effort to increase the knowledge and understanding of students at the Sunda Men's Soccer School in Sako, Palembang. This activity can increase knowledge and improve the achievements of the students of the Sunda Men's Soccer School in Sako, Palembang.